Who Climbs the Academic Ladder? Race and Gender Stratification in a World of Whiteness. Issue 3 (September 2018) - Moore, Kyle K.; Cid-Martinez, Ismael; Toney, Jermaine; Smith, Jason A.; Kalb, Amber C.; Shin, Jean H.; Spalter-Roth, Roberta M.
Under-represented minority (URM) faculty can expand the range of perspectives taught to students, but only if they are hired, granted tenure, and promoted. Their career paths can be constrained due to a stratification process that appears to legitimate a non-Hispanic White male set of rules and practices, including value neutrality and objectivity. This article measures specific aspects of human and social capital and their relationship to academic stratification in two social science disciplines, economics and sociology. Here, we measure stratification by the distribution of academic rank and examine differences based on discipline, institution type, race/ethnicity, gender, and publications in terms of academic career success. Our data are unique because they are gathered from multiple secondary sources. One contribution of this article is to measure social capital as a "two worlds" phenomenon, taken from W. E. B. Du Bois. Not surprisingly, we find that "publish or perish" still rules. Conversely, URM-oriented social capital, which can provide a safe space and opportunities to collaborate on scholarly work, is not significant. But, it may be related to feelings of satisfaction and inclusion. The only exceptions are URM-oriented sections in sociology. The article concludes with a series of policy recommendations to support URM faculty members in their careers.